Role of attitude in utilization of Jusur LMS in Saudi Arabian universities - Asiri, Mohammed J. Sherbib; Mahmud, Rosnaini; Abu Bakar, Kamariah; Mohd Ayub, Ahmad Fauzi (Elsevier, 2012)
The purpose of this study was to determine the faculty members’ utilization of Jusur LMS and their attitudes toward using Jusur LMS in Saudi Arabian universities. The article also examines whether Jusur LMS utilization is affected by attitude and demographic variables such as computer experience and age. This study is quantitative in nature and employs a descriptive co-relational research design. The sample of this study consists of 454 faculty members. Data were gathered through a questionnaire, and the findings indicated that the faculty members’ attitude is more significantly related to the utilization of Jusur LMS rather than to the demographic variables. Further analysis also reveals that the overall attitude toward Jusur LMS is significantly better at predicting frequency than the volume of Jusur LMS utilization. In addition to attitude, computer experience appears to exert only little influence on Jusur LMS utilization.